Design and Analysis of Automatic Washroom Cleaning Machine - Arvinth, Ajithkumar, Koorimugesh, Jakir Hussain (International Journal of Advanced Science and Technology, 2020)
There are many washrooms provided by the authority in the rural and urban areas but because of limited number of resources it is not possible to maintain all the cleaning assemblies from all areas so because of this we lag to maintain cleaning is these areas so all the things taken into consideration here decided to work on cleaning on washrooms of rural and urban areas. Here decided to work on a mechanism i.e. Fabrication of Advanced controlled Indian toilet sheet cleaning system .In modern world their lack man power to clean the toilet cleaning. Most of the disease is spread from toilet only .To maintains the toilet clean people can automatic toilet and normal people can use it. The disease mainly spread from washroom. Our main aim to develop the automatic toilet cleaner without man power. Now day’s people are not ready to clean the washroom and shortage of man power. To overcome this problem automatic machine more useful. Over main to create low cost machine.